Many roads lead to Rome: converging mechanisms behind tuberous sclerosis, GATORopathies, and hypothalamic hamartomas Viele Wege führen nach Rom: konvergierende Mechanismen in tuberöser Sklerose, GATORopathien und hypothalamischen Hamartomen - Kobow, Katja; Mühlebner, Angelika (Clinical Epileptology, 2026)
Tuberous sclerosis complex, GATORopathies, and hypothalamic hamartomas represent some of the most important genetically determined brain lesions associated with early-onset epilepsy. Although they differ markedly in their histological appearance, all three conditions share converging disturbances in intracellular signaling pathways that regulate cell growth, differentiation, and tissue architecture. In particular, the mechanistic target of rapamycin (mTOR) and the Sonic Hedgehog (Shh) pathway emerge as central nodes of dysregulation. Evidence from developmental biology and tumor research further suggests cross-talk between these signaling systems, raising the possibility that similar mechanisms contribute to epileptogenesis in these otherwise distinct disorders. This review summarizes histopathological features, genetic underpinnings, and signaling interactions, with a focus on their clinical implications. We highlight how the two-hit model of genetic disease and the interplay of mTOR and Shh signaling provide unifying frameworks for understanding lesion formation and epilepsy, and how this knowledge may translate into therapeutic strategies.
CRIS-Team Scopus Importer:2026-02-20
Keywords: Degeneracy; Developmental brain lesion; MAPkinase; mTOR; Sonic Hedgehog